Changing etiology and epidemiology of hepatocellular carcinoma: Asia and worldwide - Do Young Kim (Korean Liver Cancer Association, 2024)
Approximately 80% of hepatocellular carcinoma (HCC) cases arise in sub-Saharan Africa and Eastern Asia, following a similarly high prevalence of chronic hepatitis B virus (HBV) carriers in these regions. The etiology and epidemiology of HCC have recently changed worldwide. Although HBV infection is the main contributor to HCC development, a slow but continuous decline in HBV infection rates has been reported since 1990. Owing to the widespread use of direct-acting antivirals, the incidence of hepatitis C virus-related HCC has remarkably decreased in Japan and European countries. In Korea, Taiwan, and Singapore, the incidence of HBV-related HCC has significantly decreased owing to vaccination against HBV. Globally, while HBV accounted for more than half of HCCs in 1990, this had decreased to 42% in 2019. In contrast, the proportion of patients with alcoholic- and nonalcoholic steatohepatitis (NASH) increased from 13% to 18% and from 5% to 6%, respectively. NASH-related HCC has characteristics that differ from those of virus-associated HCC. Compared with other etiologies, patients with NASHassociated HCC are older, have a higher body mass index, and have higher rates of type 2 diabetes mellitus, hypertension, hyperlipidemia, and cardiovascular disease. Nonalcoholic fatty liver disease (NAFLD)-associated HCC is also known to develop in the absence of cirrhosis, unlike alcohol-related and autoimmune liver diseases. Because patients with NAFLD usually have diabetes or obesity, surveying this population is challenging. Optimal selection of the target population and surveillance tools among patients with NAFLD needs to be determined.